THE DEVELOPMENT OF RADICAL GROUPS IN INDONESIA AFTER GOVERNMENT REGULATIONS IN LIEU OF LAW NO 2/2017 CONCERNING COMMUNITY ORGANIZATION AND LAW NO 5/2018 CONCERNING TERRORISM IN NATIONAL SECURITY PERSPECTIVE - Hikam, Muhammad AS; Riyanta, Stanislaus (Indonesia Defense University, 2018)
The ratification of Government Regulation in Lieu of Law No. 2/2017 concerning Community Organization (Perppu Ormas) and Law No.5/2018 concerning Terrorism is a strategic policy achievement in the national security sector that can be utilized by the government and civil society to stem the progress of radical groups in Indonesia, especially (but not limited to) those associated with radical Islamic movements, both those who are known to use violent approaches and those who do not. Appropriate mapping of the development of radical groups, at the level of global, regional and national strategic environments, is important because it will become the basis for the formation of broader and deeper public policies related to the fight against radicalism and radical movements in the future. Descriptive qualitative analysis based on the data, documents and phenomena that occur shows that the ratification of those laws have a significant impact if followed by decisive actions by law enforcement.Keywords: radicalism, deradicalization, terrorism, Government Regulation in Lieu of Law No. 2/2017 concerning Community Organization (Perppu Ormas), Law No.5/2018 concerning Terrorism